2013
DOI: 10.1136/annrheumdis-2013-203465
|View full text |Cite
|
Sign up to set email alerts
|

Is cancer associated with polymyalgia rheumatica? A cohort study in the General Practice Research Database

Abstract: ObjectiveTo investigate the incidence of new cancer diagnoses in a community sample of patients with polymyalgia rheumatica (PMR).MethodsAll incident cases of PMR in the UK General Practice Research Database (GPRD) (1987–99), without pre-existing cancer or vascular disease and treated with corticosteroids (n=2877) were matched with up to five age, sex and GP practice patients without PMR (n=9942). Participants were followed up until first cancer diagnosis, death, transfer out of the database or end of availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 20 publications
(26 reference statements)
1
60
2
4
Order By: Relevance
“…Eight of the nine articles identified through the systematic search described cohort stud- (Table I) (15)(16)(17)(18)(19)(20)(21)(22). Two articles utilised the same dataset, but with one considering the outcomes of cancer diagnosis and the other causes of death including cancer (19,20).…”
Section: Articles Included In the Reviewmentioning
confidence: 99%
“…Eight of the nine articles identified through the systematic search described cohort stud- (Table I) (15)(16)(17)(18)(19)(20)(21)(22). Two articles utilised the same dataset, but with one considering the outcomes of cancer diagnosis and the other causes of death including cancer (19,20).…”
Section: Articles Included In the Reviewmentioning
confidence: 99%
“…Over a median follow up of 7.8 years, 23.2% of patients with PMR developed cancer compared with 19.5% of controls [Muller et al 2013]. The risk of malignancy was increased in patients with PMR during the first 6 months after diagnosis (hazard ratio 1.69; 95% confidence interval 1.18-2.42) [Muller et al 2013]. Misdiagnosis may account for these findings and this highlights the importance of careful evaluation of patients presenting with polymyalgic symptoms to exclude other conditions.…”
Section: Prognosismentioning
confidence: 99%
“…However, this may also mean that any short-term association with cancer is diluted by a lower risk of malignancy in the longer term. Indeed, the two studies in our review that specifically looked at intervals of time from PMR diagnosis showed an initial increase in the risk of malignancy, followed by a return to normal risk (5,6). Finally, we agree that a specific cohort study may well be the only way to definitively answer the question as to whether PMR is a truly paraneoplastic condition.…”
Section: Ear Editormentioning
confidence: 56%
“…tertiary care (4), primary care (5)]. Furthermore, Bellan and colleagues (2) highlight the related point of our exclusion of existing cancer in our previous study (5). Whilst we may accept that if PMR were a paraneoplastic syndrome, it does not need to occur before the malignancy is diagnosed, British guidelines for the diagnosis of PMR state that malignancy is an important differential diagnosis of polymyalgia symptoms and hence should be excluded as the cause of symptoms before a diagnosis of PMR is made.…”
Section: Ear Editormentioning
confidence: 86%